What is the clinical benefit of coronary chronic total occlusions treatment by percutaneous coronary intervention?. (2nd May 2022) - Costa, H; Mota, T; Santo, ME; Fernandes, R; Bispo, J; Carvalho, D; Palmeiro, H; Guedes, J; Mimoso, J; Vinhas, H; Jesus, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Coronary chronic total occlusions (CTO) are relatively common findings in the context of coronary angiography. The indication for revascularization of this type of lesions remains controversial. The recommendations of international cardiology societies consider the treatment of CTO by percutaneous coronary intervention (PCI) in selected patients, but this technique is not yet widely used in this context. Objectives: Characterize the patient population undergoing CTO PCI and analyze its clinical benefit. Also, try to identify patient profiles according to the composite outcome (angor, heart failure symptoms (HF), myocardial infarction (MI) or death) in short and medium term (30 days (D) and 180D). Methods: Observational and retrospective study with descriptive and comparative analysis of patients submitted to CTO PCI, between 1 January 2019 and 31 December 2020. A descriptive analysis was carried out. Chi-Square test was used for categorical variables and the T-Student test for numerical variables, with a significance level of 95%. CHIAD algorithm was applied to identify patient profiles, whose dependent variable was the presence or absence of the composite outcome (fixed 15 parent nodes- 5 children nodes). For statistical analysis, SPSS 24.0 was used. Results: N177 patients were identified, with a mean age of 65.4 years (standard deviation of 11.1), 51% were female. The most frequent location of CTO was the right coronary in 41.2%. The composite outcome occurred in 23% (30D) and 16% (180D) of patients, regardless of past medical history. Angor was present in 9.4% (30D) and 5.3% (180D); HF symptoms in 12.3% (30D) and 5.3% (180D); MI in 2% (180D) mortality in 1.8% (30D) and 4.7% (180D). The complication rate was 5.1%, mostly cardio-respiratory arrest (2.5%) and vessel dissection (1.7%). In a logic of dependence and profiles, patients with LVEF>36% (80.1%-p=0.017), without HF symptoms (82.9%-p=0.007) and non-smokers/ ex-smokers (87.6%-p=0.043), were those with the greatest benefit at 30D. Patients with a history of NSTEMI (24.5%-p=0.018) and CKD (37.5%-p=0.048) were those with most occurrences presented at 180D. Conclusion: This analysis highlights the experience of the angiography laboratory. In this pool, the majority of patients experienced evident clinical improvement and recovered in short and medium term. The rate of serious events during and after the procedure was low. This analysis suggests that the greatest benefit were found in patients with LVEF>36%, who didn´t develop post-procedure HF symptoms and in non-smokers/ex-smokers.